Supporting Double Duty Caregiving and Good Employment Practices in Health Care Within an Aging Society - Detaille, Sarah I.; de Lange, Annet; Engels, Josephine; Pijnappels, Mirthe; Hutting, Nathan; Osagie, Eghe; Reig-Botella, Adela (Frontiers in Psychology, 2020)
Abstract Background: Due to the aging society the number of informal caregivers is growing. Most informal caregivers are women working as nurses within a health organization (also labeled as double-duty caregiver and have a high risk of developing mental and physical exhaustion. Objective: The overall aim of this study was to investigate the expectations and needs of nurses in the role of double duty caregivers in the Netherlands, and to examine the meaning of self-management in managing work-life balance. Method: Firstly, a scoping review has been conducted on the topics self-management and sustainable employability of double-duty caregivers using the search engines: CINAHL, MEDLINE, PubMed, and Google Scholar. Furthermore, a qualitative study has been conducted through focus groups with double duty caregivers. Results: Twenty studies that met the inclusion criteria (i.e. nurses with double duty caregiving tasks) could be identified. We found that double duty caregivers have different motivations for being a double duty caregiver based on internal and external expectations. Double duty caregiving causes a lot of mental and physical pressure for the caregiver. To be able to combine both duty’s, double duty caregivers need flexibility and understanding from the workplace. Through two focus groups (N=17) we found that social support from the workplace is not enough to be able to manage the situation. Self-management skills are important to be able to communicate effectively with the workplace and community care organizations about the kind of support needed. Also, health care organizations should offer the same support to double duty caregivers as any other informal caregiver. Discussion: Double-duty caregivers are at high risk of developing symptoms of overload and risk of reduced self-management quality and employability levels across time. Health care organizations and the double duty caregiver often wait too long to act instead of taking more preventive measures. Furthermore, community care organizations should dialogue with double duty caregivers about their wishes concerning the division of caring tasks. This finding calls for special attention, with long-term solutions at both macro (heath-care level), organizational (meso-level) and employee level (micro level).